PENGARUH ROTASI KERJA TERHADAP KEPUASAN KERJA DALAM MEMPENGARUHI KINERJA TENAGA KEPENDIDIKAN - Warsi, Diah Aryanti Sapto (P4M STIE Putra Bangsa, 2019)
The most important resources of an organization is human resouces, those giving all energy, Tlent, creativity, and effort. It is difficult for an organization to pursue its aim without having capable human reresources. Job rotation and satisfaction are parts of quality human resources management to enhance staff performance. Rotation can inprove knowledge, capability, and minimize burmout. Job satisfaction can enhance job performance. The Purpose of this study is to investigate wheter rotation influences job satisfaction and permormance job sastifaction influences performance of 93 staffs using partial least square analysis. This study shows that rotation has asignificanly positive influences performances and rotation. Rotation is an effective way to enhance capability and knowledge, and minimize burnout, but it should consider the competency-based placement. Keyword : job rotation, job satisfaction, staff performance.